The Problems of the Development of Cultural Tourism, and the Tendency of its Development in Samarkand - Zukhra Ilkhamovna, Sattarova; Azamat Aslamovich, Sattarov; Jamshed Madjidovich, Kurbonov; Rakhima Jamshedovna, Kurbanova; Nodira Abdullaevna, Eshkuvvatova (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the development trends of cultural tourism in the city of Samarkand. The results of a questionnaire survey of foreign tourists are presented. The proposed measures and directions for the development of cultural tourism in the city of Samarkand are described.